EFEKTIVITAS MEDIA POHON ANGKA MENGGUNAKAN BAHAN ALAM TERHADAP KEMAMPUAN BERHITUNG ANAK DI PAUD KARTINI KABUPATEN BENGKULU - Nisti Wasila; Serli Marlina (STKIP Subang, 2026)
Numeracy is an important aspect of early childhood cognitive development that needs to be stimulated through engaging and concrete learning media. This study aims to test the effectiveness of a number tree media based on natural materials (branches and coffee berries) on numeracy skills and psychosocial parameters of children at Kartini Early Childhood Education (PAUD) in Kaur Regency, Bengkulu. The research method used a quantitative quasi-experimental approach with a one-group pretest-posttest design. The sample consisted of 12 children aged 4–5 years old selected via purposive sampling. Data were collected through structured observation and then analyzed descriptively and comparatively. The results showed a significant increase post-intervention. In the cognitive domain, the average score for recognizing number symbols increased from 1.8 to 3.3, and for matching quantities increased from 1.5 to 3.1 (Developing as Expected category). In the psychosocial domain, self-confidence scores jumped from 1.6 to 3.5, and learning motivation from 1.9 to 3.6 (Developing Very Well category). The high mean gain value proves that transforming abstract symbols into concrete representations of natural materials effectively overcomes mechanical memorization barriers (rotate counting) and builds children's courage. It was concluded that the natural number tree media effectively optimizes numeracy skills while strengthening children's psychosocial development.